Shiga toxin prophage analysis of clinically relevant enterohaemorrhagic E. coli isolates using Nanopore sequencing. Issue Volume 1(2019)Issue A (8th March 2019) - Yara, Daniel; Greig, David; Dallman, Tim; Jenkins, Claire
Abstract : Enterohaemorrhagic E. coli O157 produces different Shiga toxin (Stx) subtypes which can contribute to the development of disease. The advancement of severe disease such as haemolytic uraemic syndrome is significantly associated to Stx2a subtype carriage. Three distinct EHEC lineages exist, where in the UK, stx2a has found in three STEC O157 sub-lineages: Ic, I/II and IIb. Stx encoding phages from the three sub-lineages where examined to determine whether the bacteriophage which conferred the stx2a synthesis are the same or different. Relevant representative EHEC O157 strains were sequenced using the MinION Platform. The sequences were assembled and annotated, allowing Stx encoding prophage identification. Such prophages and constituent genes were then aligned for comparison along with various reference strains. Results reveal that outbreak EHEC strains carry Stx2c encoding prophages and that such prophages were conserved, supporting past studies which suggest a single integration event and clonal expansion of Stx2c bacteriophages. Analysis of Stx genes revealed that some Stx2c phages carry Stx2a encoding genes, suggesting recombination between different Stx encoding phages. Variability was observed for Stx2a encoding phages, suggesting that there are various Stx2a encoding phages circulating in the UK.